Effect of indolebutyric acid on rooting and budding of cuttings of Glyicidium sepium - Araújo Filho, Renisson Neponuceno; Primo, Dario Costa; Dias, João Lucas Aires; Marinho Junior, Josue Luiz; Piscoya, Victor Casimiro; Cunha Filho, Moacyr; Pimentel, Rejane Magalhães de Mendonça; Fernandes, Milton Marques; Pedrotti, Alceu; Holanda, Francisco Sandro Rodrigues; et al. (Journal of Environmental Analysis and Progress, 2019)
Studies carried out with the use of gliricidia biomass found that green manure contributes to increasing the productivity of forest crops when compared to the incorporation of other legumes. This study aimed to evaluate the viability of vegetative propagation by cuttings in the development of rooting and budding of Glyicidium sepium in different concentrations of indolebutyric acid (IBA). The experiment was carried out in a greenhouse with an entirely randomized block design and increasing concentrations of IBA 0, 625, 1250, and 3000 mg.L-1 with six replicates. The cuttings were standardized in length and diameter, then treated with sodium hypochlorite and immersed in different concentrations of IBA. The parameters plant evaluated were the sprouts number, sprouts length, sprouts diameter, sprouts dry weight, and roots dry weight. The concentration of IBA was shown to be effective in increasing all parameters studied at the IBA concentration of 2100 mg.L-1, and the higher concentrations did not offer any cost-benefit advantages for the production of gliricidia by cutting.